(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
In the article problems in the internal areas of residential buildings in Tashkent and other large cities of Uzbekistan were considered. Foreign and domestic experience in the reconstruction of courtyards of multi-story residential buildings was analyzed.